Bruce Bronzan for State Assembly Fundraiser at The Star Palace - Watkins, Howard::::::::: (1979)
Guests standing outside due to fire in building; ?, Laurie Leifer, Judy Soley in wheelchair, ?, Doug Jones, ?, ?, ? and Clyde Jones in plaid jacket